Quantifying the Performance of Individual Players in a Team Activity - Duch, Jordi; Waitzman, Joshua S.; Amaral, Luís A. Nunes (PLOS ONE, 2010)
Background Teamwork is a fundamental aspect of many human activities, from business to art and from sports to science. Recent research suggest that team work is of crucial importance to cutting-edge scientific research, but little is known about how teamwork leads to greater creativity. Indeed, for many team activities, it is not even clear how to assign credit to individual team members. Remarkably, at least in the context of sports, there is usually a broad consensus on who are the top performers and on what qualifies as an outstanding performance. Methodology/Principal Findings In order to determine how individual features can be quantified, and as a test bed for other team-based human activities, we analyze the performance of players in the European Cup 2008 soccer tournament. We develop a network approach that provides a powerful quantification of the contributions of individual players and of overall team performance. Conclusions/Significance We hypothesize that generalizations of our approach could be useful in other contexts where quantification of the contributions of individual team members is important.